Confronting Farmers’ Perceptions of Climatic Vulnerability with Observed Relationships between Yields and Climate Variability in Central Argentina - Hernandez, Valeria (2015)
Farmers’ perceptions of climate variability is compared with the sensitivity of observed yields for wheat, maize, soybean, and sunflower crops to interannual and intra-annual climate variability in two districts (Junín and San Justo) in central Argentina from the 1970s. A recent transition occurred here between mixed crop and livestock farming to a more specialized system, dominated by transgenic soybean combined with glyphosate. According to the ethnographic fieldwork, farmers ranked drought first and flood second as the main adverse climate factors in both districts. Overall, the farmers’ representations fit rather well with the observed relationships between interannual variability of yields and rainfall, especially in Junín. The adverse impact of long-lasting dry spells, especially during the first half of the crop cycle, is usually combined with the more linear impact of large rainfall amounts (anomalously positive/negative rainfall amounts associated with anomalously positive/negative yields) during the second half of the crop cycle. This relationship is strong for soybeans, similarly large for maize, far weaker for wheat, and reversed for sunflower, which is the only crop that benefits, on average, from anomalously low rainfall amounts at a specific stage of the crop cycle. The adverse effect of flood on soybeans and maize seems less phase-locked and more diluted across the crop cycle. This paper presents the argument that climate and society have a complex relationship, requiring an integrated analysis of the social context, people’s perceptions of climate, and scientific climate knowledge. The concept of “climate social significance” is proposed in order to highlight the strategies implemented by different socioproductive groups to address adverse climate events.